Generation and reactions of aryloxy and diaryloxycarbenes - Lu, Xiaosong (My University, 2001)
The research work presented is mainly in the area of the physical organic chemistry of nucleophilic aryloxy and diaryloxycarbenes and their potential in synthetic applications. Some other intermediates, including dipolar intermediates or radicals, were also involved. 2,2-Diaryloxy-Δ3 -1,3,4-oxadiazolines and 2-aryloxy-2-methoxy-Δ 3 -1,3,4-oxadiazolines were synthesized by oxidation of the corresponding aryloxy or alkoxy carbonyl hydrazones of acetone followed by acid-catalysed exchange with different phenols. Subsequent thermolysis processes resulted in the generation of differently substituted diaryloxycarbenes and aryloxycarbenes. Cycloreversion to 2-diazopropane and corresponding carbonates was shown to be a competitive route. The intermolecular reaction of the diaryloxy or aryloxycarbenes with an electron-deficient alkyne, DMAD, resulted in interesting dioxyvinylcarbenes, which did a novel intermolecular aromatic substitution. A mechanistic study showed that the substitution was nucleophilic. A further study of the ortho substituent effect on the ipso aromatic substitution revealed a novel electronic effect, a through-space stabilization of a vinylogous dioxycarbene by an electron rich group. This interesting result has not been reported before. Its synthetic application needs further study. Thermolysis of a 2-acetoxy-2-aryloxy oxadiazoline resulted in some products that could only have come from radical reactions. Without any good radical stabilizing group, the fragmentation of a dioxycarbene to radical pairs is surprising.
Keywords: Chemistry; Chemistry